Antibacterial mechanism of artemisinin / beta-cyclodextrins against methicillin-resistant Staphylococcus aureus (MRSA). (May 2018) - Lin, Lin; Mao, Xuefang; Sun, Yanhui; Cui, Haiying
Abstract: A new inhibitor to overcome the multi-drug resistance of MRSA was developed in this study. Artemisinin (ART) was encapsulated in beta-cyclodextrin (β-CD) in order to enhance the solubility of ART. The molecular encapsulation of ART was confirmed by using Fourier transform infrared (FT-IR), differential scanning calorimetry (DSC), X-Ray Diffraction (XRD), and nuclear magnetic resonance ( 1 H NMR) methods. The phase solubility study showed the relationship between ART solubility and β-CD concentration. The antibacterial activity of ART/β-CDs inclusion complexes (ART/β-CDs-IC) (20 mg/mL) against MRSA was distinguished, with the inhibition rate of 99.94% after 4 days. The antibacterial mechanism research indicated the membrane permeability of MRSA can be increased by the complexes. Besides, the respiratory metabolism of MRSA was inhibited via Embden-Meyerhof-Parnas (EMP) pathway. The conclusion was further confirmed by measuring the contents of three enzymes in the irreversible reaction in EMP pathway. The obtained results enable the potential use of ART/β-CDs-IC in the field of antimicrobial. Highlights: ART embedded into β-CDs as guest molecule and the solubility of ART increased by β-CDs. ART/β-CDs inclusion complexes exhibited antibacterial activities against MRSA. ART/β-CDs improved the permeability of MRSA membrane. ART/β-CDs inhibited respiratory metabolism of MRSA through EMP pathway.